Piezo1-related physiological and pathological processes in glioblastoma - Fu, Weijia; Hou, Xue; Ding, Lijuan; Wei, Jiaying; Hou, Wei (Frontiers in Cell and Developmental Biology, 2025)
IntroductionGlioblastoma (GBM) is the most malignant of the astrocytomas, primarily involving the cerebral hemispheres and cerebral cortex. It is one of the fatal refractory solid tumors with a 5-year survival rate of only 5% in adults. Cells in biological tissues are subjected to mechanical forces, including hydrostatic pressure, shear stress, compression and tension. Cells can convert mechanomechanical signals into biological or electrical signals, a process known as mechanical signaling. Piezo1 channels, members of the Piezo family of mechanosensitive ion channels, can be directly activated by mechanical stimuli alone, mediating mechanosensitive cation currents that activate subsequent signaling pathways. Studies have shown that Piezo1 is largely unexpressed in normal brain tissues but is expressed at high levels in glioblastoma and can significantly contribute to glioblastoma development and progression, but its role in the pathogenesis of glioblastoma remains unclear.MethodsWe reviewed the relevant literature and data in six major databases including PubMed, EMBASE, CINAHL, Scopus, Web of Science and TCGA. Finally, a total of 126 papers were selected for review and analysis (Search terms include: glioblastoma, piezo1, biomechanical, targeted therapy, mechanomechanical, extracellular matrix, radiation therapy and more). The role of piezo1 in the development of glioblastoma was summarized.ResultsPiezo1 affects several fundamental pathophysiological processes in glioblastoma, such as tissue sclerosis, angiogenesis, energy supply, and immune cell infiltration, and can be used as an indicator of malignancy and prognosis in patients with glioblastoma, as well as a therapeutic target to control tumor progression.DiscussionThe pathological mechanism of piezo1 in glioblastoma is very complex, and the aberrant expression of piezo1 plays a very important role in the development of glioblastoma. Specific mechanistic studies focusing on Piezo1 will help us understand the mechanobiology of glioblastoma and help us develop new therapeutic approaches for glioblastoma patients.